Pharmacokinetics of capmatinib in participants with hepatic impairment: A phase 1, open‐label, single‐dose, parallel‐group study. Issue 1 (18th June 2021) - Chen, Xinhui; Cui, Xiaoming; Pognan, Nathalie; Quinlan, Michelle; Kapoor, Shruti; Rahmanzadeh, Gholamreza; Giovannini, Monica; Marbury, Thomas C.
Abstract : Aims: Capmatinib, a mesenchymal–epithelial transition factor tyrosine kinase inhibitor, is metabolized by cytochrome P450 (CYP) 3A4 and aldehyde oxidase. In individuals with hepatic impairment, alterations in hepatobiliary excretion and metabolism could lead to higher capmatinib exposure. We compared the pharmacokinetics of a single oral dose of capmatinib 200 mg administered to participants with varying degrees of hepatic impairment vs . matched controls with normal hepatic function. Methods: This phase 1, multicentre, open‐label, parallel‐group study enrolled adult participants with normal hepatic function and mild, moderate and severe hepatic impairments. Eligible participants received a single oral dose of 200 mg capmatinib. The pharmacokinetic parameters of capmatinib were analysed and compared across participants with impaired and normal hepatic function. Results: Of 31 enrolled participants, 29 had an evaluable pharmacokinetic profile: normal ( n = 9); mild ( n = 6); moderate ( n = 8); severe ( n = 6). Compared with the normal group, geometric mean (GM) maximum (peak) observed plasma drug concentration after single‐dose administration decreased by 27.6% in the mild group (GM ratio [GMR] = 0.724; 90% confidence interval [CI]: 0.476–1.10), by 17.2% in the moderate group (GMR = 0.828; 90% CI: 0.563–1.22) and remained unchanged in the severe group (GMR = 1.02; 90% CI: 0.669–1.55). Compared with the normal group, GM area under the plasma concentration–time curve from time zero to infinity decreased by 23.3% in the mild group (GMR = 0.767; 90% CI: 0.532–1.11), by 8.6% in the moderate group (GMR = 0.914; 90% CI: 0.652–1.28) and increased by 24% in the severe group (GMR = 1.24; 90% CI: 0.858–1.78). Conclusion: Mild, moderate and severe hepatic impairment did not have a clinically relevant impact on capmatinib pharmacokinetics. No new safety findings are reported in this study.